Photoperiodic regulation of pituitary thyroid-stimulating hormone and brain deiodinase in Atlantic salmon. (1st January 2021) - Irachi, Shotaro; Hall, Daniel J.; Fleming, Mitchell S.; Maugars, Gersende; Björnsson, Björn Thrandur; Dufour, Sylvie; Uchida, Katsuhisa; McCormick, Stephen D.
Abstract: Seasonal timing is important for many critical life history events of vertebrates, and photoperiod is often used as a reliable seasonal cue. In mammals and birds, it has been established that a photoperiod-driven seasonal clock resides in the brain and pituitary, and is driven by increased levels of pituitary thyroid stimulating hormone (TSH) and brain type 2 iodothyronine deiodinase (DIO2), which leads to local increases in triiodothyronine (T3 ). In order to determine if a similar mechanism occurs in fish, we conducted photoperiod manipulations in anadromous (migratory) Atlantic salmon ( Salmo salar ) that use photoperiod to time the preparatory development of salinity tolerance which accompanies downstream migration in spring. Changing daylength from short days (light:dark (LD) 10:14) to long days (LD 16:8) for 20 days increased gill Na + /K + -ATPase (NKA) activity, gill NKAα1b abundance and plasma growth hormone (GH) levels that normally accompany increased salinity tolerance of salmon in spring. Long-day exposure resulted in five-fold increases in pituitary tshβb mRNA levels after 10 days and were sustained for at least 20 days. tshβb mRNA levels in the saccus vasculosus were low and not influenced by photoperiod. Increased daylength resulted in significant increases in dio2b mRNA levels in the hypothalamus and midbrain/optic tectum regions of the brain. The results are consistent with the presence of a photoperiod-driven seasonal clock in fish which involves pituitary TSH, brain DIO2 and the subsequent production of T3, supporting the hypothesis that this is a common feature of photoperiodic regulation of seasonality in vertebrates. Highlights: We show for the first time that pituitary transcription of tshβb is responsive to increased daylength. Photoperiod induction of pituitary tshβb is followed by increased brain transcription of dio2b, plasma GH and gill NKA activity. The results are consistent with the pituitary TSH – brain DIO2 axis controlling the photoperiodic control of seasonality in fish.